Performance Study of Block ACK and Reverse Direction in IEEE 802.11n Using a Markov Chain Model - Hossain, MA; Sarkar, NI; Gutierrez, J; Liu, W (Elsevier, 2017)
IEEE 802.11n networks are widely used in home and corporate network environments because they offer high-speed wireless Internet access at relatively low-cost. The 802.11n standard introduced several key features including Block acknowledgement (ACK) and reverse direction (RD) data transmission for enhanced system performance. An in-depth study of 802.11n system capacity for Block ACK mechanisms (both protected and unprotected) and RD data flows is required to assist optimum planning and design of such systems in view of the limited wireless channel capacity. In this paper we study the interdependencies of Block ACK and RD mechanisms using a discrete bi-directional Markov chain model under non-saturated traffic loads. We present a mathematical model to derive throughput, delay, and packet loss probability for both protected and unprotected Block ACKs under varying loads. We validate the model using MATLAB based numerical studies. Results obtained show that the combined effect of protected Block ACK and RD flows has a positive impact on system performance. However, unprotected Block ACK wastes transmission opportunity (TXOP) especially in collisions and therefore degrades the system performance. Our findings reported in this paper provide some insights into the performance of 802.11n with respect to Block ACK and RD methods. This study may help network researchers and engineers in their contribution to the development of next generation wireless LANs such as IEEE 802.11ac.
Keywords: Block ACK; Distributed coordination function; Markov chain; Medium access control; Reverse direction